Measures of financial development - Hoffman, Dieter (Research of GSB, 2018)
The subject of financial development has received a great deal of attention, both theoretically and through empirical research. Earlier work focussed on the relationship between financial development and economic growth, with both policy makers and academics seeing financial liberalisation and the development of financial systems as a way to quickly improve the welfare of a country's citizens. Practically the steps taken to liberalise and develop financial systems have had mixed results, indicating the pitfalls of any 'one size fits all' approach to development. Still, there is almost unanimous acceptance of a strong linkage between the financial system and the wider economy. Financial development in Africa is also of particular interest given the economic challenges that many African countries face (and related issues such as poverty). Financial development can act as a lever to spur economic growth and ultimately the welfare of much of the continent. However, it is widely recognised that African financial systems are under-developed. Allen et al. (2013) show that even compared to other developing economies, African financial systems score significantly lower across most measures of development. More recent studies have therefore shifted focus towards answering questions related to the determinants and drivers of financial development itself. Given the accepted benefits of an effective financial system, what policies and interventions can be put in place to assist with financial development? Ultimately, any inquiry into the realm of financial development is constrained by the study's ability to select the appropriate indicators for, and accurately measure the financial system. Even under ideal circumstances this can be challenging, as there is certainly no consistent view as to how best measure financial development. Approaches have changed over time, from traditionally focussing on simply the size and depth of a financial market to more modern indicators related to stability and financial inclusion – more aligned to the long term welfare outcomes in the economy rather than merely measuring the properties of a system. In reality, studies have to account for inconsistent and often missing data sets, especially for developing economies (which tend to be the focus of research into development). The assertion of La Porta et al. (1998) that measuring the size of financial markets "is a bit tricky" somewhat understates the challenges related to the measurement of financial systems. This study aims to explore the theory and empirical studies related to financial development, its impact on economic growth in Africa and the various ways to measure financial markets and institutions. The rest of this report is structured as follows; Section 2 contains the context and case for the study and lays out the objectives for the research. It also provides a summary overview of the key functions of financial systems as a reference for the rest of the paper. Section 3 provides a comprehensive review on the literature around three core areas (1) The relationship between financial development and economic growth, (2) the determinants of financial development and (3) the approaches to measuring financial development. Section 4 contains the discussion on this study's methodology and hypotheses. Section 5 discusses the key results and findings from the analysis. Section 6 provides a conclusion and recommendations for future research, followed by the Appendices.